AB0275 Differences in The Clinical Evaluation of Joints in Patients with Rheumatoid Arthritis and Secondary Sjögren Syndrome. (15th July 2016) - Romanowska-Prόchnicka, K.; Olesińska, M.; Paradowska-Gorycka, A.; Felis-Giemza, A.; Mańczak, M.; Szukiewicz, D.
Abstract : Background: Secondary Sjögren syndrome (sSS) is classified as a connective tissue disease characterized mainly by xerophthalmia and xerostomia, and accompanied by various autoimmune diseases such as rheumatoid arthritis (RA), systemic lupus erythematosus, scleroderma, vasculitis, mixed connective tissue disease, primary biliary cirrhosis or autoimmune thyroiditis. Objectives: To investigate whether a difference exists between DAS28 from CRP and DAS28 from ESR in patients with rheumatoid arthritis (RA) and secondary Sjögren syndrome (sSS). Methods: The study included patients with rheumatoid arthritis (RA) and secondary Sjögren syndrome (sSS). The inclusion criteria have been specified as follows: radiological confirmation of rheumatoid arthritis, presence of data on DAS28-CRP and DAS28-OB, presence of at least one subjective and one objective symptom of dryness, and also presence of specific antibodies or at least focus score one in biopsy. Results: Disease activity score 28 (DAS28) was assessed using both ESR and CRP in 60 patients with RA and sSS and 59 patients with RA alone. Although concordance between these two methods was good (Cohen's kappa coefficient κ=0.60, 95% of CI (0.45–0.75) in first group and κ=0, 71, 95% of CI (0.56–0.86) in control group). In the group with RA and sSS mean value of DAS28-ESR=5.2, whereas mean value of DAS28-CRP=4.7 (p<0.0001). In the group with RA alone mean DAS-ESR=4, 7 while mean DAS-CRP=4, 6, no significant difference was identified. Moreover, in RA patients with sSS mean ESR=39mm/h compared with mean CRP at 25mg/dl. 79% of all patients demonstrated dysproteinemia. There were connections between higher ESR and dysproteinemia. In control group there were no significant difference between CRP and ESR. Conclusions: Both DAS28-ESR and DAS28-CRP are useful outcome measures in RA. However, in patients with RA and sSS DAS28 should be evaluated based on CRP or SDAI. Disclosure of Interest: None declared